(untitled) (Jurnal Manajemen dan Ekonomi (JME), 2025)
This research aims to investigate the role of traditional market revitalization as a strategy to develop sales of MSME products in Bengkala Village, Buleleng Regency. Through an internal market study, this research explores the potential of traditional markets in supporting the growth of MSMEs and strengthening the local economy. The research method used is a qualitative approach with case studies, through in-depth interviews with market traders, visitors and village government. Data analysis was carried out using qualitative methods, with a focus on identifying challenges and opportunities in the revitalization of traditional markets and their impact on sales of MSME products. Research findings show that the revitalization of traditional markets has the potential to increase sales of MSME products by expanding market reach, increasing local community involvement, and promoting the diversity of local products. The implication of this research is the importance of paying attention to traditional markets as one of the main distribution channels for MSMEs and encouraging revitalization efforts to maximize the potential of traditional markets in supporting local economic growth.